2011
DOI: 10.1007/s00436-011-2261-3
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity of essential oils of Zingiber officinalis and Achyranthes aspera against mosquitoes

Abstract: Due to the global health problems associated with mosquito-borne diseases, over two million people primarily in the tropical countries are at risk. The widely and commonly used chemical method though effective, has some major disadvantages making insect control practically difficult. In view of the above, it is unavoidable to search for new molecules, which are eco-friendly, cheaper, and safer. The present study deals with evaluation of bioactive potential of two commonly occurring plants against mosquitoes pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…They are generally recognized as safe by the US Food and Drug Administration. It is acknowledged that many essential oils and compounds derived from various essential oils can exert toxic activity against mosquito species (Araujo et al 2003;Amer and Mehlhorn 2006;Bhat and Kempraj 2009;Gu et al 2009;Pavela et al 2009;Conti et al 2010;Koliopoulos et al 2010;Elango et al 2011;Khandagle et al 2011;Pitarokili et al 2011;Shwetha and Chandrashekar 2011). During our mass screening program for new agrochemicals from the wild plants, essential oil of Saussurea lappa C.B.Clarke (Syn.…”
Section: Introductionmentioning
confidence: 98%
“…They are generally recognized as safe by the US Food and Drug Administration. It is acknowledged that many essential oils and compounds derived from various essential oils can exert toxic activity against mosquito species (Araujo et al 2003;Amer and Mehlhorn 2006;Bhat and Kempraj 2009;Gu et al 2009;Pavela et al 2009;Conti et al 2010;Koliopoulos et al 2010;Elango et al 2011;Khandagle et al 2011;Pitarokili et al 2011;Shwetha and Chandrashekar 2011). During our mass screening program for new agrochemicals from the wild plants, essential oil of Saussurea lappa C.B.Clarke (Syn.…”
Section: Introductionmentioning
confidence: 98%
“…The adverse effects of synthetic chemical insecticides in the environment have received wide public concern [7] . Over the last five decades, many problems have been resulted due to the misuse of synthetic insecticides in Agriculture and Public Health Programs, viz.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this paper present a better adulticide activity for M. greenmaniana essential oil in comparison with metanolic and aqueous extracts. There have been just few studies regarding botanical products that have revealed the adulticide effect against sandflies in comparison with mosquitoes (Amóra et al 2009;Pandey et al 2009;Khandagle et al 2011;Pitarokili et al 2011;Prophiro et al 2012). This is probably due to the difficulties of maintenance and availability of sandfly colonies (Yaghoobi-Ershadi et al 2006).…”
Section: Discussionmentioning
confidence: 96%